2009
DOI: 10.3390/molecules14114358
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ripeness and Drying Process on the Polyphenols and Tocopherols of Pistacia vera L.

Abstract: This paper highlights, for the first time, the changes in the phenolics fraction (anthocyanins, flavonoids and stilbenes) and tocopherols of unpeeled Pistacia vera L. var. bianca with ripening, and the effect of the sun-drying process. The total polyphenol levels in pistachios, measured as mg of Gallic Acid Equivalent (GAE), were: 201 ± 10.1, 349 ± 18.3 and 184.7 ± 6.2 mg GAE/100 g DM in unripe, ripe and dried ripe samples, respectively. Most phenolics in ripe pistachios were found to be anthocyanins. They inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 41 publications
4
61
3
1
Order By: Relevance
“…Monagas et al (15) reported the catechin content and Del Rio et al (38) reported monomeric and oligomeric flavan-3-ols, flavonols, dihydrochalcones and phenolic acids in hazelnut skins. Although these studies did not report polyphenol content in terms of whole hazelnuts, monomeric and oligomeric (5) 2052 (28,80,86,92) 2713·49 (10 -12,18,28) 493·90 (1) 233·52 (70,169,170,175) ND Pine nuts 206 26 (5) ND 0·03 (11,12) 1 (11,13,18,43) § 190·75 (70,169,170,175,189,190) ND Pistachios 703 22 832 (5,50,87) 1·27 (191) 136·45 (10 -12,18,40,42,43,191) 252·71 (1) 189·43 (70,88,169 -171,175,192) 803·22 (40,43,48,49) Walnuts 1602 21 (5) 39·11 (44,51,60,193,194) 0·54 (11,12,…”
Section: Total Phenols and Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monagas et al (15) reported the catechin content and Del Rio et al (38) reported monomeric and oligomeric flavan-3-ols, flavonols, dihydrochalcones and phenolic acids in hazelnut skins. Although these studies did not report polyphenol content in terms of whole hazelnuts, monomeric and oligomeric (5) 2052 (28,80,86,92) 2713·49 (10 -12,18,28) 493·90 (1) 233·52 (70,169,170,175) ND Pine nuts 206 26 (5) ND 0·03 (11,12) 1 (11,13,18,43) § 190·75 (70,169,170,175,189,190) ND Pistachios 703 22 832 (5,50,87) 1·27 (191) 136·45 (10 -12,18,40,42,43,191) 252·71 (1) 189·43 (70,88,169 -171,175,192) 803·22 (40,43,48,49) Walnuts 1602 21 (5) 39·11 (44,51,60,193,194) 0·54 (11,12,…”
Section: Total Phenols and Flavonoidsmentioning
confidence: 99%
“…, Grippi et al (49) and Ballistreri et al (40) have reported on the stilbene content of pistachios but these data have yet to be submitted or included in the PE database. Other tree nuts may contain stilbenes, but a systematic analysis of their abundance is lacking.…”
Section: Stilbenesmentioning
confidence: 99%
“…However, the low production is compensated for by the very high quality (Bellomo & Fallico 2007). The Italian pistachio, which comes from Bronte (Southern Italy) and represents approximately 80% of the Italian production with just one variety (Bianca), shows, at ripeness, a red-violet skin while retaining a green nutmeat (Ballistreri et al 2009). Usually, it is picked fully ripe and sold as a green product.…”
mentioning
confidence: 99%
“…Ballistreri ve ark. [43], E vitamini bakımından antepfıstığında en fazla ɣ-tokoferol tespit etmişlerdir. Ayrıca olgunluk ve kurutma aşaması sırasında toplam ɣ ile α tokoferollerin azaldığını ve ɣ-tokoferolün antioksidan aktivitesinin α-tokoferole göre daha yüksek olduğunu bildirmişlerdir.…”
Section: Antepfıstığının Vitamin İçeriğiunclassified